Understanding Friction and Wear Behavior at the Nanoscale of Aluminum Matrix Composites Produced by Laser Powder Bed Fusion. Issue 2 (7th November 2019) - Lorusso, Massimo; Aversa, Alberta; Marchese, Giulio; Calignano, Flaviana; Manfredi, Diego; Pavese, Matteo
Abstract : Laser powder bed fusion (LPBF) is an additive manufacturing (AM) technique for the fabrication of components with a complex design, and it is particularly appropriate for structural applications in automotive and air‐space industries. Aluminum matrix composites (AMCs) are promising materials for these uses because they are ductile, light weight, and have an excellent strength‐to‐weight ratio. Herein, a study on microstructure, hardness, and the nanoscale tribological properties of the AlSi10Mg alloy with and without ceramic particles is presented. AMCs are realized with different compositions: 10 wt% of microsize TiB2, 1 wt% of nanosize TiB2, 0.5 wt% of nanosize SiO2, and 0.5 wt% of nanosize MgAl2 O4 . It is found that the nanocomposites show a lower coefficient of friction (COF), whereas in the case of microsize TiB2 reinforcement, the COF is higher than with either nanosize reinforcements or AlSi10Mg alloy without reinforcement. Results indicate that the interfacial bond between the matrix and the particles of the ceramic reinforcement has a crucial role in wear processes. Abstract : The tribological characterization at nanoscale through the nanoscratching of AlSi10Mg alloy and some of its composites, obtained by laser powder bed fusion (LPBF), is described. Using such a technique, aluminum matrix composites (AMCs) are made with different compositions: 10 wt% of microsize TiB2, 1 wt% of nanosize TiB2, 0.5 wt% of nanosize SiO2, and 0.5 wt% of nanosize MgAl2 O4 .